2011
DOI: 10.1152/ajpendo.00560.2010
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of mineralocorticoid blockade on the hypothalamo-pituitary-adrenal axis in pregnant and nonpregnant ewes

Abstract: Lingis M, Richards EM, Keller-Wood M. Differential effects of mineralocorticoid blockade on the hypothalamo-pituitary-adrenal axis in pregnant and nonpregnant ewes. Am J Physiol Endocrinol Metab 300: E592-E599, 2011. First published January 4, 2011; doi:10.1152/ajpendo.00560.2010.-During pregnancy, plasma ACTH and cortisol are chronically increased; this appears to occur through a reset of hypothalamo-pituitary-adrenal (HPA) activity. We have hypothesized that differences in mineralocorticoid receptor activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
4
1
1
Order By: Relevance
“…38,39 Both Ucn2 and CA treatments enhanced plasma cortisol levels in the present study. A stimulatory effect of MR blockade by CA on the hypothalamus-pituitary-adrenocortical axis is consistent with previous reports, 34,40 whereas the Ucn2-induced rise in cortisol may be because of an attendant increase in plasma Ucn1 (which we have formerly shown occurs after Ucn2 administration 12 presumably as a consequence of competition for the CRF 2 receptor) with subsequent activation of CRF 1 and the hypothalamus-pituitary-adrenocortical axis. 41 Although hypothalamus-pituitary-adrenocortical activation is obviously not salutary, this consequence of Ucn2 administration has been shown to be a transient event (unlike the more sustained hemodynamic, vasoactive hormone, and renal responses) both previously 15 and in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…38,39 Both Ucn2 and CA treatments enhanced plasma cortisol levels in the present study. A stimulatory effect of MR blockade by CA on the hypothalamus-pituitary-adrenocortical axis is consistent with previous reports, 34,40 whereas the Ucn2-induced rise in cortisol may be because of an attendant increase in plasma Ucn1 (which we have formerly shown occurs after Ucn2 administration 12 presumably as a consequence of competition for the CRF 2 receptor) with subsequent activation of CRF 1 and the hypothalamus-pituitary-adrenocortical axis. 41 Although hypothalamus-pituitary-adrenocortical activation is obviously not salutary, this consequence of Ucn2 administration has been shown to be a transient event (unlike the more sustained hemodynamic, vasoactive hormone, and renal responses) both previously 15 and in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…We found that CA had little impact on either PRA or plasma Ang IIresults comparable to those reported by other investigators after acute MR antagonism, 25,33,34 and although a stimulatory effect of CA on renin secretion might have been anticipated secondary to the fall in arterial pressure, this may have been countered by the concomitant renin-inhibitory increase in sodium excretion. In contrast, Ucn2, both alone and in combination with CA, significantly reduced circulating levels of both PRA and Ang II.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…MR antagonists administered intracerebroventricularly increase ACTH and/or corticosterone in rats (8,66,90,217,238,297) and MRmediated effects appear to occur over a time course of 20 min to 1 h. This is consistent with the higher affinity of the MR as compared to the GR for cortisol or corticosterone, which has been demonstrated in all species studied (243,246,249,256), and results in relatively high receptor occupancy in vivo even at basal concentrations (279). MR blockers also increase ACTH in the sheep, a species with high MR occupancy under basal conditions (186,249). In humans, inhibition of evening ACTH concentrations after administration of an oral MR agonist has been shown; this is a time when endogenous MR occupation would be low (27).…”
Section: Role Of Mr and Gr In Delayed Feedbacksupporting
confidence: 70%
“…Our previous studies suggest that alterations in corticosteroid feedback effects through mineralocorticoid action and increased sensitivity to stresses, such as perceived hypovolemia, are more likely contributors to the increase in plasma ACTH (30). In contrast, our results do indicate that the role of serotonin in control of appetite may be altered in pregnancy.…”
Section: Effects On Feedingcontrasting
confidence: 69%